Farm-level and socio-economic impacts of a genetically modified subsistence crop : the case of smallholder farmers in KwaZulu-Natal, South Africa - Kirsten, Johann F. (University of Pretoria, 2013)
Thesis (PhD)--University of Pretoria, 2012.